Schizophrenia; Recent Cognitive and Treatment Approaches Using Induced Pluripotent Stem Cells - Nassim Rastgar (International Clinical Neuroscience Journal, 2020)
One of the most severe mental disorder which leads to a disturbance in the percipience of reality is named schizophrenia. Schizophrenia is a combination of hallucinations, delusions, and mental disorders that the severity of them impairs healthy thinking and behavior, and in general, the inability to perform daily activities. Behavioral, intellectual, and emotional disorders indicate the widespread impact of schizophrenia on various aspects of mental health. Schizophrenia’s signs and symptoms of schizophrenia are varied, although delusions, hallucinations, or disorganized speech included in common symptoms. Dopamine has been the main subject of much research on schizophrenia for decades. Molecular neuroimaging studies to explore the dopamine system (DA system) in vivo have revealed that Schizophrenia is first associated with a defect in the striatum and then with a defect in extrastriatal regions with centralizing on cortex and midbrain. Also, the gamma-aminobutyric acid (GABA) mRNA dysregulation and neuroinflammatory mechanisms can be useful in schizophrenia. Various medications such as antipsychotic drugs used to the aim of treating this disease, but they can just decline or improve the positive symptoms. Modeling neurodevelopment and synaptic connection defects by induced human pluripotent stem cells have made appropriate circumstances to eliminate schizophrenia treatment barriers. With the development of cell therapies and induced pluripotent stem cells (iPSCs), there is a hope that the negative symptoms can be improved.